Genetic evidence for a noncanonical function of seryl-tRNA synthetase in vascular development - Herzog, Wiebke; Mueller, Katja; Huisken, Jan; Stainier, Didier Y. R. (Circulation Research, 2009)
In a recent genetic screen, we identified mutations in genes important for vascular development and maintenance in zebrafish (Jin et al. Dev Biol. 2007;307:29-42). Thirty-two mutations at the adrasteia (adr) locus cause a pronounced dilatation of the aortic arch vessels as well as aberrant patterning of the hindbrain capillaries and, to a lesser extent, intersomitic vessels. This dilatation of the aortic arch vessels does not appear to be caused by increased cell proliferation but is dependent on vascular endothelial growth factor (Vegf) signaling. By positional cloning, we isolated seryl-tRNA synthetase (sars) as the gene affected by the adr mutations. Small interfering RNA knockdown experiments in human umbilical vein endothelial cell cultures indicate that SARS also regulates endothelial sprouting. These analyses of zebrafish and human endothelial cells reveal a new noncanonical function of Sars in endothelial development. © 2009 American Heart Association, Inc.
CRIS-Team Scopus Importer:2020-09-23
Keywords: Angiogenesis; SerRS; Seryl-tRNA synthetase; Vascular dilatation; Zebrafish